ANALISIS KEPUASAN SERTA KESELAMATAN PENGGUNA JASA JAK LINGKO/MIKRO TRANS - Muhammad Riva’I; Awwal Ghaniy Putra Siswanto, Radityo Farrelyno, Jonatan Steven Simamora (Jurnal Ekonomi dan Bisnis, 2024)
This research aims to analyze the level of satisfaction and safety of Jak Lingko/Mikro Trans service users in Jakarta. Using quantitative survey methods, data was collected from 25 respondents who are active users of this service. This research measures user satisfaction based on several indicators, including comfort, affordability, timeliness and service quality. In addition, safety aspects are analyzed through user perceptions of physical and operational security while using the service. The research results show that although most users are satisfied with the affordability and convenience of the service, there are still concerns regarding safety, especially at night and in certain areas. It is hoped that these findings can provide input for the government and Jak Lingko/Mikro Trans managers in improving service quality and user safety in the future.